Anonymous
Anonymous asked in Science & MathematicsEngineering · 1 decade ago

Solve k= k+15 divided by 3(k-1) use quadratic formula?

Solve k= k+15 divided by 3(k-1) use quadratic formula

3 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    k = (k+15)/3*(k-1)

    ==> multiply both sides by 3(k-1) to get rid of fractions

    3k(k-1) = k+15

    ==> expand the LHS

    3k^2-3k = k+15

    ==> move everything to the LHS

    3k^2-4k-15=0

    actually this does factor into (3k+5)(k-3), but if you want to use the formula, just use:

    a=3, b=-4 and c=-15

    x = -(-4) +/- sqrt[(-4)^2-2*3*(-15)] / 2*3

    x = 4 +/- sqrt(196) / 2*3

    x = 4 +/- 14 / 6

    ==> factor out a 2 from top and bottom

    x = 2 (2 +/- 7) / 2*3

    ==> cancel the twos to get

    x = 2 +/- 7 / 3

    which gives 2+7 / 3 and 2-7 / 3 which gives 3 and -5/3

  • 1 decade ago

    multiply by 3(k-1)

    3k^2 - 3k = k + 15

    3k^2 - 4k + 15 = 0

    quadratic equation

    x = (-b +/- sqrt(b^2 - 4*a*c)) / (2a)

    answers are

    x1 = 0.66667 + 2.1344 i

    x2 = 0.66667 - 2.1344 i

    you're right math, missed a sign change on 15

  • leo
    Lv 6
    1 decade ago

    multiply by 3(k-1)

    3k(k-1)=k+15

    3k^2-3k-k-15=0

    3k^2-4k-15=0

    k=3 or k=-1.67

Still have questions? Get your answers by asking now.